Strengthening Religious-Based Character Education In Forming Kamil People In The School/Madrasah Environment - Hartono, Riadi; Majidah, Siti (AS-SUNNIYYAH, 2024)
Character education is a basic education that must be formed from an early age. The initial foundation of character education is in the family. Meanwhile, the school is an educational institution in charge of continuing and developing the character of children. This study aims to determine the application of religious-based character education in the Islamic Education Kencong village at the Elementary School level. This type of research is qualitative research whose data is obtained from observation, open questionnaires, interviews, and documentation. The results of this study indicate that religious-based character education is implemented through the Maqoman Mahmudan program and the Evereday program with Al Quran. Some character education strategies carried out are: 1) Exemplary; 2) Learning; 3) Empowerment and civilization; 4) Strengthening; and 5) Assessment. 6) Communication. Why should character education be integrated into religious education? Because the role of religion can meet human needs in terms of directing, mentoring, and balancing the character of students. Equipped with a strong character education base, students will later become a generation of character and eventually become kamil people, in accordance with educational ideals.